Pra Adjudikasi Terhadap Pelaku Tindak Pidana Penganiayaan Anak - Rusli Banapon (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
The investigation process has been carried out and a suspect has been named as an alleged criminal act of abuse against children. This research is a normative juridical research on this problem and then examines and knows the answers to this problem through a concept approach, statutory approach and case approach then from the results of the description conclusions and suggestions can be drawn. The results of this research and problem analysis use the Law Enforcement Concept, which is an initial framework for thinking about Pre-Adjudication Juridical Analysis of Offenders of Child Abuse. The results of the study show that the implementation of pre-adjudication procedures by the Weet Police as Investigators in handling complaints of abuse against children as indicated in the Letter of Determination of Suspect Number: S.Tap/02/III/2020/ POLSEK, on ​​15 February 2020 in the criminal justice system should be implemented in an integrated manner (integrated/synchronized) so that the delegation of stage one to the Public Prosecutor can be followed up, but from 2020 to 2023 the BAP along with the suspects and evidence has not been submitted to the Public Prosecutor's Office of Southwest Maluku District Court to be transferred to the Saumlaki District Court to carry out an Examination hearing and obtain a Court Decision and legal remedies taken by the suspect in the alleged crime of child abuse in Tounwawan Village in the pre-adjudication stage.